Penanaman Modal Indonesia Versus Malaysia dari Segi Hukum Positif dalam Studi Banding di Malaysia - Rizki Bima Anggara; Risma Apriyanti; Nada Prima Dirkareshza; Atik Winanti (Politika Progresif : Jurnal Hukum, Politik dan Humaniora, 2025)
As countries located in the Asian region, Malaysia and Indonesia each have their own investment appeal. Over time, many investors have shown a stronger preference for investing in Malaysia rather than Indonesia. This phenomenon is influenced by various factors, making it a compelling subject of study. This research aims to examine the distinguishing factors in the investment appeal of Malaysia and Indonesia, particularly from the perspective of the positive legal systems in both countries. The objective of this study is to understand the legal regulations governing investment in Indonesia and Malaysia and to determine which regulatory framework is more attractive to investors. The research employs a normative juridical method using a comparative law approach. Data were collected from primary legal materials such as legislation and secondary sources such as books, journals, and previous studies through a literature review. The data were then analyzed descriptively and comparatively. The research findings indicate that Malaysia's investment regulatory framework is more attractive to investors compared to that of Indonesia. This is primarily due to the greater stability of Malaysia’s investment regulations and their relatively infrequent sudden changes. Furthermore, Malaysia’s legal system, which is based on common law, offers greater flexibility to foreign investors. The ease and stability of regulations in Malaysia make it a more preferred investment destination. These findings offer valuable input for the Indonesian government to improve its investment regulatory framework.